The prevalence of obesity and metabolic syndrome in Tibetan immigrants living in high altitude areas in Ladakh, India. Issue 4 (July 2018) - Lin, Belle Yanyu; Genden, Karma; Shen, Wei; Wu, Po-Shu; Yang, Wen-Chien; Hung, Hui-Fang; Fu, Chun-Min; Yang, Kuen-Cheh
Summary: Objective: To examine the prevalence of obesity and related cardiovascular disease risk factors among Tibetan immigrants living in high altitude areas. Research methods & procedures: A total of 149 Tibetan immigrants aged 20 years and over were recruited in 2016 in Ladakh, India. Anthropometric indices and biochemical factors were measured. Using the provided Asia-Pacific criteria from the World Health Organization, overweight and obese status were determined. Metabolic syndrome (MetS) was defined according to the American Heart Association. Results: In general, men were older, taller, and had a greater amount of fasting glucose, and uric acid when compared to women. The prevalence of overweight, general obesity, and central obesity was 23.4, 42.6, and 42.6% in men and 7.8, 64.7, and 69.6% in women, respectively. The prevalence of MetS was 10.6% in men and 33.3% in women, respectively. In older subjects, the prevalence of obesity and MetS was found to be greater. In both genders, the prevalence of hypertension, central obesity, and MetS was significantly different among these body mass index (BMI) groups. Compared to the non-central obesity group, the central obesity group has higher weight, BMI, body fat, hip circumference, systolic and diastolic BP, and prevalence of hypertension. No relationship was found between the prevalence of diabetes and fasting glucose and BMI groups or central obesity groups in both genders. Conclusions: Among this group of Tibetan immigrants living in high altitude areas, women have a higher prevalence of obesity and MetS than men. No relationship was found between diabetes and obesity.